Strengthening Information Networking Literacy Through Digital Collaboration Models in the United States - Zeqiu Xu (CV Edujavare Publishing, 2025)
The rapid development of digital technology has transformed communication patterns, information exchange, and collaborative interaction in educational and community environments. This community service program aims to strengthen information networking literacy through digital collaboration models inspired by practices implemented in the United States. The program employed a qualitative participatory approach involving university students, educators, and community members as participants. The implementation stages included needs analysis, socialization, digital literacy training, mentoring, and evaluation activities. Participants were introduced to various collaborative digital platforms such as Google Workspace, Zoom, Microsoft Teams, and online networking media to improve communication competence, information-sharing skills, and collaborative interaction. The results of the program indicated that participants experienced significant improvement in digital literacy awareness, communication effectiveness, and the ability to utilize digital collaboration tools for academic and professional purposes. In addition, participants demonstrated greater understanding of ethical communication, information verification, and responsible participation in digital environments. The program also strengthened participants’ confidence in engaging with online networking activities and collaborative learning systems. Despite several challenges such as technological inequality and varying levels of digital competence, continuous mentoring and participatory learning approaches contributed positively to the success of the activities. Overall, the implementation of information networking literacy through digital collaboration models provides valuable opportunities for improving community empowerment, educational interaction, and digital participation in the contemporary information era. The experiences and collaborative practices implemented in the United States can serve as important references for developing sustainable digital literacy programs in educational and community service contexts.